ASSESSMENT OF QUALITY HUNTING LANDS USING REMOTE SENSING DATA - Svetlana Anatolievna Trautvain; Sergey Aleksandrovich Dragunov (Наука. Инновации. Технологии, 2022)
The article assesses the quality of public hunting grounds 26:18:10 "No-voaleksandrovskogo", which includes the results of feld inventory-site and decryption of high-resolution satellite images from a variety of sources in the composition of the navigation software SAS.Planet, study the map of the Internet resources of the Public cadastral map. On the basis of remote sensing data clarifes the boundaries of the territory and area of the elements of habitat hunting species of animals. In the land, it is recommended to develop hunting on 3 main types of hunting resource: 1) brown hare, 2) partridge, 3) pheasant. For each species identifed suitable habitat with good forage and protective nesting characteristics. The results appraisal habitats have shown that high-quality habitats is the main form of hunting (hare) is on the "medium" level. The quality of the land on a grey partridge and pheasant - are "average". Therefore the farming of these kinds of promising.